Determinan Keunggulan Kompetitif dan Kinerja Industri Kreatif - Widiya Dewi Anjaningrum; Agus Purnomo Sidi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
The purpose of this study is to determine the effect of market orientation, innovation and product creativity on the performance of creative industries to achieve competitive advantage. This research is a field research case study on creative-preneur industries incorporated in Malang Creative Fusion (MCF). Sample was chosen by non probability sampling with purposive sampling approach that are creative-preneur industries that have willing to be respondents and can provide information needed in the study amounted to 133 respondents. The result of the research shows that market orientation, innovation and product creativity have positive and significant influence to the performance of creative industry to achieve competitive advantage. The managerial implications of the results of this study are that in order to achieve competitive advantage in highly competitive environments, creative-prenur industries should improve industry performance by optimizing market orientation, not just focusing on what can be produced, but also looking at what the customer wants, competitors, how to coordinate across the internal functions of the industry and think about its impacts for both consumers and the environment. Creative-prenur industries should also try to find new, unique and original creative products, or at least develop existing products, strive for products to have their own character, quality and high attractiveness.